The Impact Of The Soviet Financial And Monetary System In The Social Life Of The Population Of Uzbekistan (In The 20-30s Of The 20th Century) (Global Scientific Review, 2026)
This study explores the impact of the Soviet financial and monetary system on the social life of the population of Uzbekistan during the 1920s–1930s. Following the establishment of the Uzbek Soviet Socialist Republic in 1925, comprehensive reforms, including nationalization of land and water and monetary regulations, were implemented to align the republic with Soviet economic policies. The research examines how these measures influenced agricultural production, resource allocation, and social relations, highlighting both the intended objectives of modernization and the unintended consequences on local communities. Particular attention is paid to the redistribution of property, changes in land ownership, and the effects of centralized economic planning on the daily lives of ordinary citizens. The findings indicate that while the reforms aimed to integrate Uzbekistan into the socialist framework, they also led to social tension, economic dislocation, and challenges in implementing Soviet monetary policies. This study contributes to a deeper understanding of the early Soviet economic system’s social ramifications in Central Asia.